Perancangan Produk Standing Frame (Alat Terapi Berdiri) Bagi Penyandang Disabilitas Cerebral Palsy - Septiana Sinurat, Artha; Ayu Siagian, Ester; Sitanggang, Franciscus; Agustina Panjaitan, Kathrin Rut; Manalu, Lyandry; Uly Tampubolon, Nathasya Dona; Manalu, Windy; Simamora, Yenny Adriyanti; Siboro, Benedikta Anna Haulian (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2023)
Cerebral palsy is a neuromotor developmental disorder that often occurs in children. The treatment of cerebral palsy is widely done through physical therapy, behavioral therapy, speech therapy, nutrition, medicine and surgical interventions. This study aims to design a therapeutic tool for people with cerebral palsy disabilities in the form of Standing Frame to help the patient's muscles heal in order to stand well. The method is house of quality (HOQ) and ergonomic approach. To obtain specifications that reflect the expected quality dimension, comparative studies and gap analysis of similar products are conducted. Questionnaire processing results show the customer requirements, attributes that are considered very important for consumers, namely sturdy anchoring poles, comfortable to use, anti-slip, economical price and safe to use. From the results of technical requirements analysis attributes that are prioritized to be technical requirements in product development, namely unloading pairs, retaining materials / belt feet and hands made of fabric, locking / rollers (locking retratos) strong, strong ribbon / webbing parts and wheel shafts. The sizes of this therapy tool use indonesian anthropometry size for children aged 6-12 years As an additional feature this tool is equipped with a table and wheels to facilitate the putting of something and facilitate the mobility of the tool. This tool is designed with a disassembly system in order to fit the user's body. For safety in use, this tool is equipped with a belt that can be tightened to stabilize the user's position at the time of use and equipped with foam for comfortable use.